A review of recent progress in the synthesis of bio-indigoids and their biologically assisted end-use applications - Choi, Kwon Young (Dyes and Pigments, 2020)
Indigo is one of the oldest known dyes and is a major component of dyes used for coloring jeans their classical blue hue. Traditionally, indigo was extracted from indigo-producing plants, but synthetic indigo has been in use since the development of efficient chemical syntheses, and presently, various indigo isomers and derivatives can be readily synthesized. Indigo can undergo an electron transfer accompanied by a distinct color change, due to a redox reaction made possible by its chemical structure and intramolecular organization. In addition, it exhibits excellent biocompatibility and biodegradability. Its versatile functionality has inspired extensive research into indigo-derived chemicals for various applications over the past few decades. This review provides an overview of the recent indigoid applications in medical, cosmetic, and food industries, as well as in the manufacture of functional fibers, polymers, semiconductors, and sensors. This study also addresses the limitations of indigo applications, including those related to natural indigo, eco-friendly bio-dyes, and chemo-indigo.
Keywords: Color changes; Eco-friendly; Electron transfer; End-uses; Food industries; Functional fibers; Recent progress; Indigo; Indigo applications; Indigo dyeing; Indigo polymers; Indigo semiconductor; Indigo sensor